Optimalisasi Sistem Pengadaan Bahan Baku Oleh Team Stocker Untuk Meningkatkan Efisiensi Operasional Mie Gacoan Kartasura - Franola Asokawati; Ari Susanti (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
This study aims to analyze the optimization of the raw material procurement system by the stocker team in improving operational efficiency at Resto Mie Gacoan Kartasura. The background of the study is based on the importance of the availability of raw materials in the right quantity and time to support smooth production and service quality. The study used a qualitative approach with data collection techniques through interviews, observation, and documentation. Informants consisted of the restaurant manager, the stocker team, and kitchen employees who were selected purposively. The results of the study indicate that the procurement system has been implemented in a structured manner through sales data-based planning, stock recording using the GTS digital system, and the application of the FIFO and FEFO principles in inventory management. The role of the stocker team has proven significant in maintaining stock accuracy, smooth distribution of materials, and controlling operational costs. However, obstacles still encountered in the form of inconsistencies in stock data, delays in supplier supplies, and high workloads. Therefore, continuous optimization is needed through improving record-keeping discipline, strengthening inter-department coordination, and evaluating supplier performance to support operational efficiency and improve service quality.